The influence of conventional and novel blanching methods on potato granules, phytochemicals, and thermal properties of colored varieties - Saini, Rajni; Kaur, Sukhpreet; Aggarwal, Poonam; Dhiman, Atul (Frontiers in Nutrition, 2023)
Introduction Colored potatoes comprise many bioactive compounds that potentially support human health. Polyphenols present in them have associated therapeutic benefits like antimutagenic and anticarcinogenic properties. Method The current study aimed to explore the effects of different blanching methods (steam blanching, hot water blanching, and microwave-assisted blanching) on the phytochemical and structural aspects of PP-1901 and Lady Rosetta (LR) potato varieties. Changes in the antioxidant activity, color, total ascorbic acid, phenolic, and flavonoid content were based on the variations in parameters including temperature (blanching using hot water and steam) and capacity 100– 900 W (blanching using microwave). Results For both PP-1901 and LR varieties, all the blanching methods led to a significant reduction in residual peroxidase activity, as well as affecting their color. The preservation of bioactive substances exhibited a microwave steam>hot water blanching trend. Blanching significantly increased the antioxidant activity of all the samples. Additionally, Fourier-transform infrared spectroscopy revealed that phytocompounds were retained to their maximum in microwave-blanched samples, especially at 300 W. The type of blanching method significantly affected the thermal properties of potatoes by disrupting the ordered structure of the matrix. Discussion Microwaves at 300 W can be used as a novel and suitable alternative technique for blanching potatoes, which successfully retained the original quality of it in comparison to steam and hot water blanching.